Evaluasi Usability Aplikasi Perangkat Bergerak Sipindo menggunakan Metode Think Aloud dan Heuristic Evaluation - Prasetyo Margaret Wibisono; Retno Indah Rokhmawati; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Sipindo mobile application (Sipindo Indonesia Information System) is an agricultural application that provides easy access to android-based agricultural information that is Indonesian agriculture. From the grouping of problems using the Heuristic Evaluation method found by users, a total of 46 problems were found. The most problems found by users are in the principle of match between system and the real world which amounts to 14 problems, visibility of system status which amounts to 11 problems, User control and freedom which amounts to 8 problems, aesthetic and minimalist design which amounts to 7 problems, error prevention which amounts to 5 problems, and recognition rather than recall which amounts to 1 problem. grouping problems using the Think Aloud method that users found found a total of 55 problems using the Severity rating table. The most problems found by users are found in task 1 as many as 13 problems, Task 4 as many as 12 problems, task 5 as many as 8 problems, task 6 as many as 7 problems, task 7 as many as 7 problems, task 8 as many as 4 problems, task 3 as many as 3 problems, and task 2 as many as 1 problem.